THE SOCIAL LIFE OF FORMER CONVICTS (Social Adaptation in Society for Former Convicts Under Founding of Rehabilitation Center Class II City of Tanjungpinang) - -, Miswanto (ASKETIK, 2018)
Itâs a hardly for former convicts to get their place back in society, so they must adapt to society in order to get back a normal life with others. But in fact they are ostracized indeed by society. The readiness to do social adaptation is very difficult because former convicts are always feel ostracized by society, moreover they are feel isolated in social interaction with others where they are live in. The goal of this research is to know how social adaptation in society for former convicts under founding of Rehabilitation Center Class II City of Tanjungpinang. The method of this research is descriptive qualitative which give a full view of phenomenon of what is happened in field. The population of this research is 22 people, which use proposive sampling to get 9 people as the sample, consist of informant and key informant. Data collecting by observation, interview and documentation, which will be analized by use data analysis from Mattew B. Milles and A. Michael Huberman. Former convicts who have finish their time of imprisonment and have to go back to society, must adapt to a life with new regulations and they must know how to react if there are social problems happened. Former convicts will be acceptable in society depend on their ability to adapt with others. It is also happened to former convicts who have to go back to society with a social status as an ex-prisoner and they have to change point of view of society to them. Former convicts have to show off their positive attitudes by doing better, polite, diligent in praying and not unwilling to help society.